Evaluating the incidence and risk factors for ventriculoperitoneal shunt sepsis at Dr George Mukhari Academic hospital in Pretoria, South Africa - Andries Pretorius; Adrian Kelly; Patrick Lekgwara (Interdisciplinary Neurosurgery)
Introduction: Patients with increased pressure hydrocephalus are a common referral to the Department of Neurosurgery at our institution. Materials and methods: A descriptive cross-sectional study performed by consecutively enrolling 335 subjects who underwent a ventriculoperitoneal shunt insertion between the 01 January 2014 – 30 November 2022, aimed to establish our local ventriculoperitoneal shunt sepsis incidence, and further evaluate the known risk factors for ventriculoperitoneal shunt sepsis at 3- month follow-up. Results: In our study 335 ventriculoperitoneal shunts were inserted, 190 (57 %) were inserted in children and 145 (43 %) were inserted in adults. With regards the cause of hydrocephalus in 90/335 (26.9 %) subjects this was congenital, in 45/335 (13 %) subjects this was a primary intra-axial CNS tumor, in 40/335 (12 %) subjects this was intraventricular hemorrhage, and in 38/335 (11 %) subjects this was in subjects with a myelomeningocele. Considering the ventriculoperitoneal shunt infection incidence 28/335 (8.4 %) subjects developed this complication within 3 months of the procedure. In evaluating the significance of the known risk factors for ventriculoperitoneal shunt sepsis, our study demonstrated that having a ventriculoperitoneal shunt insertion performed in the emergency theatre (p = 0.02, OR 1.87, CI 0.83–4.23), having a ventriculoperitoneal shunt inserted at night (p = 0.03, OR 3.92, CI 1.13–13.58), having a history of ventriculoperitoneal shunt sepsis (p = 0.004, OR 7.34, CI 2.20–24.55), being clinically immunosuppressed at the time of the ventriculoperitoneal shunt insertion procedure (p = 0.03, OR 3.01, CI 1.09–8.32), and having a post-operative cerebrospinal fluid leak (p = 0.04, OR 5.19, CI 0.91–29.71), demonstrated significance in predicting that ventriculoperitoneal shunt sepsis would occur. Conclusion: Our study confirmed that our institutional ventriculoperitoneal shunt sepsis rate is 8.4 % and furthermore confirmed the significance of several of the known risk factors as taken from the literature.